2017
DOI: 10.1159/000477755
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy Revisited: Hemodialysis Catheter Malposition in the Left Ascending Lumbar Vein

Abstract: In selected cases, cuffed tunneled catheters via the iliac vein are implanted as a last resort access for hemodialysis. To monitor the correct position, sonography of the inferior vena cava (IVC) is sufficient in most cases. Position control using an X-ray of the abdomen is not routinely recommended when femoral catheters are implanted. In this report, we describe the case of a 59-year-old patient on chronic hemodialysis due to granulomatosis with polyangiitis and complex shunt history with multiple shunt occl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…3,4 However, CTHC inserted into the ALV via FV is a rarer malposition. 5,8 As in our case, the possibility of malposition of the catheter to the ALV is higher in interventions performed through the left FV, due to the wider angle between the left ALV and CIV. 9 Findings such as difficulties in advancing the guide wire or catheter, insufficient blood flow in aspiration, and sudden lower back pain during insertion suggest catheter malposition.…”
Section: Discussionmentioning
confidence: 45%
See 3 more Smart Citations
“…3,4 However, CTHC inserted into the ALV via FV is a rarer malposition. 5,8 As in our case, the possibility of malposition of the catheter to the ALV is higher in interventions performed through the left FV, due to the wider angle between the left ALV and CIV. 9 Findings such as difficulties in advancing the guide wire or catheter, insufficient blood flow in aspiration, and sudden lower back pain during insertion suggest catheter malposition.…”
Section: Discussionmentioning
confidence: 45%
“…7 However, complications such as malposition and dysfunction have been reported after catheterization through FV. [3][4][5] In our case as well, malposition developed in both catheter interventions, and late diagnosis could be made since no evaluation was made with fluoroscopy or x-ray immediately after the procedure.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…[40][41][42] In the present review, only 3 of 36 patients were reported to have received a US and/or undergone fluoroscopy to guide catheterization. 1,4,8 At the practical operational level, the above-mentioned image guidance techniques for LE catheterization have limited option ranges and unsatisfactory degrees of effectiveness. [43][44][45] The absence of real-time image guidance was an important technical cause of misplacement.…”
Section: Catheterization Proceduresmentioning
confidence: 99%